Dyslipidemia in Pregnancy-Induced Hypertension - Mohtarin, Sabreena (Journal of Enam Medical College, 2024)
Pregnancy-induced hypertension (PIH) is a leading cause of maternal mortality and morbidity. Abnormal lipid profile and increased lipid peroxidation activate endothelial dysfunction causing PIH. Estimation of lipid profile in pregnancy may be helpful in predicting the development of PIH and further progression. Early diagnosis of dyslipidemia may prevent PIH thereby preventing obstetric complications. Dyslipidemia is known to be associated with essential hypertension but their role in PIH remains unclear. Early identification of at-risk women may help in taking timely preventive and curative management to prevent pregnancy related complications. J Enam Med Col 2022; 12(1): 50−53